Public participation in mental health programming: insights into the ways young people are involved in the development, delivery, and evaluation of mental health initiatives in school and community spaces - Sarah Dolaty; Emily Midouhas; Jessica Deighton; Matthew P. Somerville (International Journal of Adolescence and Youth)
Despite recent investments in England’s school mental health initiatives, these interventions continue to face challenges in sustainability and relevance. Youth participation in developing, delivering, and evaluating services can enhance their fit within school and community contexts. While evidence highlights the benefits of youth participation, little is known about the engagement approaches used as part of these mental health interventions. This study applied Davies’s (2009) Matrix Model to categorize 76 mental health participation activities across six local authorities in England. Findings reveal variations in youth influence and decision-making across participation methods, outlining key characteristics, aims, and features as reported by professional stakeholders. The results emphasize the need for intentional and transparent selection of participation approaches that align with programme goals. These insights have practical implications for school leaders, mental health researchers, intervention developers, and educational stakeholders seeking to integrate meaningful youth participation into mental health initiatives.